VALPROATE INDUCED HYPERAMMONEMIC ENCEPHALOPATHY - Qayyum, Wajeeha; Yousafzai, Zaland Ahmed; Iqbal, Muhammad Shahid; Khan, Sohail; Amin, Qazi Kamran; Shafiq, Ihtesham (Journal of Ayub Medical College Abbottabad, 2022)
Valproate is a commonly prescribed anticonvulsant drug. It has a potential to cause hyperammonemia even in the presence of normal liver function tests. This hyperammonemic state can lead to encephalopathy referred as Valproate induced hyperammonemic encephalopathy (VHE). Here we present a case of valproate induced hyperammonemic encephalopathy in a young male caused by initiation of valproate therapy.